DAMPAK GEMPA BUMI DI SULAWESI BARAT DAN UPAYA MITIGASI - Supartoyo; Hilman Suwargana; Arnan Karim (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
On Friday of January 15, 2021 at 19:23 local time, the Mamuju area and its surroundings were hit by a destructive earthquake with a magnitude of 6.2 Mw (moment magnitude) which resulted disaster, which are : 105 people died (95 people in Mamuju Regency and 10 people in Majene Regency), 3,369 people were injured, about 3,750 buildings were damaged in Mamuju Regency and 4,172 buildings were damaged in Majene Regency. In addition, there are present of collateral hazard include ground crack, liquefaction and landslide. The maximum of earthquake intensity scale occurred in the Mamuju area of VII MMI (Modified Mercally Intensity). Seventeen months later, on Wednesday, June 8, 2022, at 12:32:36 local time, the Mamuju area and its surroundings were again hit by a destructive earthquake with a magnitude of 5.8 Mw. This earthquake also resulted disaster, which are : 17 people were injured, many buildings and 70 houses were damaged in Mamuju Regency. The earthquake intensity scale of V MMI. The two destructive earthquakes event give lessons learn of the importance for earthquake mitigation efforts. The results of field observations show that earthquake mitigation efforts have not been optimal in the West Sulawesi area. The fact that people still panicked during the earthquake and the amount of damage to buildings. Earthquake mitigation efforts through structural and non-structural mitigation must be increased in the West Sulawesi area to reduce the risk if an earthquake repeat in the future.